Microcomputed tomographic, biomechanical and histological analyses of lumbar interbody fusion with iliac crest bone graft in a pig model - Krtička, Milan; Nekuda, Vladimír; Ira, Daniel; Sedláček, Radek; Suchý, Tomáš; Kavková, Michaela; Břínek, Adam; Göpfert, Eduard; Bilik, Andrej; Kaiser, Jozef; Křen, Leoš; Plánka, Ladislav (University of Veterinary Brno, 2021)
The main goal of this study was to assess the progress of vertebral stability after lumbar interbody fusion related to microcomputed tomography (micro CT), biomechanical analysis, and histological assessment towards spine fusion. Twelve male pigs were used; each underwent L2-3 discectomy and implantation of an iliac crest bone graft in two groups; six spines were harvested eight weeks (A1) and six spines 16 weeks (A2) after surgery (7 native spines for biomechanical analysis). The CT was performed by GE phoenix datos vertical bar x 2.0 with a sample drift correction. The samples were divided according to fusion quality. Biomechanical evaluation was carried out on the MTS Mini Bionix testing system. In the nondestructive mode, three cycles of pure bending moments were applied (5 Nm load limit) at a rate of 20 degrees/min in flexion (+40 degrees) and extension (-40 degrees). Two representative histological sections from four samples were obtained (A1, n = 2; A2, n = 2); areas of mature bone were quantified. In micro CT, better results were achieved in group A2 (not significant). Eight weeks after the operation, flexural stiffness decreased to 48% of its initial value for native cadavers (P < 0.05); after 16 weeks it was comparable to native cadavers, demonstrating the suitability of the implanted graft (P < 0.05). The newly formed bone tissue occupied an average area of 94.205 mm(2) (A1) and 26.240 mm(2) (A2). It was confirmed that micro CT, biomechanical analysis, and histological assessment are technically feasible and suitable for the evaluation of results of other methods of large bone defect treatment.

The main goal of this study was to assess the progress of vertebral stability after lumbar interbody fusion related to microcomputed tomography (micro CT), biomechanical analysis, and histological assessment towards spine fusion. Twelve male pigs were used; each underwent L2-3 discectomy and implantation of an iliac crest bone graft in two groups; six spines were harvested eight weeks (A1) and six spines 16 weeks (A2) after surgery (7 native spines for biomechanical analysis). The CT was performed by GE phoenix datos vertical bar x 2.0 with a sample drift correction. The samples were divided according to fusion quality. Biomechanical evaluation was carried out on the MTS Mini Bionix testing system. In the nondestructive mode, three cycles of pure bending moments were applied (5 Nm load limit) at a rate of 20 degrees/min in flexion (+40 degrees) and extension (-40 degrees). Two representative histological sections from four samples were obtained (A1, n = 2; A2, n = 2); areas of mature bone were quantified. In micro CT, better results were achieved in group A2 (not significant). Eight weeks after the operation, flexural stiffness decreased to 48% of its initial value for native cadavers (P < 0.05); after 16 weeks it was comparable to native cadavers, demonstrating the suitability of the implanted graft (P < 0.05). The newly formed bone tissue occupied an average area of 94.205 mm(2) (A1) and 26.240 mm(2) (A2). It was confirmed that micro CT, biomechanical analysis, and histological assessment are technically feasible and suitable for the evaluation of results of other methods of large bone defect treatment.
Microcomputed tomographic, biomechanical and histological analyses of lumbar interbody fusion with iliac crest bone graft in a pig model
Keywords: Bone replacement; spine; injury; Bone replacement; spine; injury